2002
DOI: 10.1021/ja0283044
|View full text |Cite
|
Sign up to set email alerts
|

The [4Fe−4S]2+ Cluster in Reconstituted Biotin Synthase Binds S-Adenosyl-l-methionine

Abstract: The final step of the biotin biosynthetic pathway is catalyzed by biotin synthase (BioB) and involves the insertion of sulfur into dethiobiotin. The discovery that [2Fe-2S] 2+ clusters in as-isolated BioB can be converted into [4Fe-4S] 2+ clusters under reducing conditions, 1 coupled with the requirement of S-adenosyl-L-methionine (SAM) for activity in vitro and the conserved C-X 3 -C-X 2 -C cluster-binding motif, led to speculation that BioB was a member of the radical SAM family of enzymes, 2 that utilize a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
45
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 60 publications
(56 citation statements)
references
References 15 publications
11
45
0
Order By: Relevance
“…However, for the latter spectrum, a change in the isomer shift of the non-cysteine-ligated iron atom (from ␦ 2 ϭ 0.57 (3) mm/s to ␦ 2 ϭ 0.68 (3) mm/s) was observed, which indicates that AdoMet only binds at one iron of the cluster, namely this unique, non-cysteine-ligated iron atom. AdoMet binding to this unique iron site of the [4Fe-4S] cluster was previously observed by Mössbauer studies of PFL-AE (17) and biotin synthase (18). Furthermore, our results from the Mössbauer spectrum of HemN in the presence of AdoMet are consistent with the observed coordination of AdoMet to the iron-sulfur cluster in the crystal structure of E. coli HemN (5) in which it was observed that AdoMet binds at the iron by means of the carboxyl and the amino group of the methionine part of AdoMet.…”
Section: Resultssupporting
confidence: 64%
See 1 more Smart Citation
“…However, for the latter spectrum, a change in the isomer shift of the non-cysteine-ligated iron atom (from ␦ 2 ϭ 0.57 (3) mm/s to ␦ 2 ϭ 0.68 (3) mm/s) was observed, which indicates that AdoMet only binds at one iron of the cluster, namely this unique, non-cysteine-ligated iron atom. AdoMet binding to this unique iron site of the [4Fe-4S] cluster was previously observed by Mössbauer studies of PFL-AE (17) and biotin synthase (18). Furthermore, our results from the Mössbauer spectrum of HemN in the presence of AdoMet are consistent with the observed coordination of AdoMet to the iron-sulfur cluster in the crystal structure of E. coli HemN (5) in which it was observed that AdoMet binds at the iron by means of the carboxyl and the amino group of the methionine part of AdoMet.…”
Section: Resultssupporting
confidence: 64%
“…The iron-sulfur clusters of several members of the family have been characterized by electron paramagnetic resonance (EPR), resonance Raman, and Möss-bauer spectroscopy (7)(8)(9)(10)(11)(12)(13)(14)(15)(16). For pyruvate formate-lyase-activating enzyme (PFL-AE) and biotin synthase (BioB), it was shown using Mössbauer spectroscopy that the [4Fe-4S] cluster contains one iron atom, which is not ligated by a cysteine residue, and that AdoMet binds to this special iron site of the cluster (17,18). Later, AdoMet binding was studied in detail by EN-DOR spectroscopy for PFL-AE and lysine 2,3-aminomutase (LAM) (19 -21).…”
mentioning
confidence: 99%
“…Thus far two members of the AdoMet-dependent family of FeS-containing radical enzymes have been structurally characterized by x-ray crystallography, biotin synthase (BioB) and coproporphyrinogen III oxidase (HemN) (60,61), and both confirm the mode of binding of AdoMet to the unique iron site of the [4Fe-4S] cluster proposed based on spectroscopic studies (57,58). In the case of biotin synthase, the assembly of two FeS clusters at different binding sites has been demonstrated: an oxygen-sensitive [4Fe-4S] 2ϩ,ϩ cluster ligated by a CX 3 CX 2 C motif that binds AdoMet and an air-stable [2Fe-2S] cluster ligated by three conserved cysteines and an arginine residue in a CX 30 CX 59 CX 71 R arrangement (42,59,(61)(62)(63). While the physiological relevance of the [2Fe-2S] cluster in recombinant biotin synthase is still a subject of debate, it has been shown to be capable of providing the sulfur for biotin formation in a single turnover experiment (64 -66).…”
Section: Discussionmentioning
confidence: 99%
“…Crystallographic studies have demonstrated that AdoMet binds to the unique iron of the active site [4Fe-4S] 2ϩ cluster in radical-AdoMet enzymes via the methionine amide and carboxylate groups (16) and this is manifest by 3-4 cm Ϫ1 upshifts in both dominant bands in the resonance Raman spectrum, i.e. the symmetric breathing mode of the [4Fe-4S] core and the asymmetric stretching mode of the terminal Fe-S(Cys) ligands (17). These bands are observed at 336 and 356 cm Ϫ1 , respectively, in reconstituted anSMEcpe and upshift to 339 and 360 cm Ϫ1 , respectively, on addition of excess AdoMet.…”
Section: Figure 4 Resonance Raman Spectra Of Ansmecpe As Isolated (Amentioning
confidence: 99%